Ecology and morphological characterization of gametophyte and 'Chantransia' stages of Sirodotia huillensis (Batrachospermales, Rhodophyta) from a stream in central Mexico - Carmona, Javier; Montejano, Gustavo; Necchi Júnior., Orlando (Wiley, 2006)
The morphology and phenology of Sirodotia huillensis was evaluated seasonally in a central Mexican first-order calcareous stream. Water temperature was constant (24-25°C) and pH circumneutral to alkaline (6.7-7.9), and calcium and sulfates were the dominant ions. The gametophyte stages were characterized by the presence of a distinctive mucilaginous layer, a marked difference in phycocyanin to phycoerythrin ratio between female and male plants, and the presence of a carpogonia with a large trichogyne (>60 μm). Occasionally three capogonia were observed on a single basal cell. The 'Chantransia' stages were morphologically similar to those described for the other members of Batrachospermales. A remarkable observation was the formation of dome-shaped structures, consisting of prostrate filaments that are related with the development of new gametophytes. Chromosome numbers were n = 4 for fascicle cells, cortical filament cells and dome-shaped cells, and 2n = 8 for gonimoblast filament cells and 'Chantransia' stage filaments. Gametophytes and 'Chantransia' stages occurred in fast current velocities (60-170 cm/s) and shaded (33.1-121 μmol photons/m2/s) stream segments. The population fluctuated throughout the study period in terms of percentage cover and frequency: the 'Chantransia' stages were most abundant in the rainy season, whereas gametophytic plants had the highest frequency values during the dry season. These results were most likely a result of fluctuations in rainfall and related changes in current velocity. Some characteristics of this population can be viewed as probable adaptations to high current velocities: the mucilaginous layer around plants that reduces drag; potential increase in fertilization by the elongate and plentiful trichogynes and abundant dome-shaped structures producing several gametophytes.
Keywords: 'Chantransia' stages; Batrachospermales; Ecology; Gametophyte; Morphology; Rhodophyta; Sirodotia huillensis; Stream; gametophyte; morphology; phenology; red alga; water temperature; Mexico [Mexico (NTN)]; Mexico [North America]; North America; Chantransia; Trichogyne